Black‐Phosphorus‐Incorporated Hydrogel as a Conductive and Biodegradable Platform for Enhancement of the Neural Differentiation of Mesenchymal Stem Cells. (30th July 2020) - Xu, Chao; Xu, Yin; Yang, Ming; Chang, Yukai; Nie, Anmin; Liu, Zhongyuan; Wang, Jianglin; Luo, Zhiqiang
Abstract: Conductive hydrogel scaffolds have important applications for electroactive tissue repairs. However, the development of conductive hydrogel scaffolds tends to incorporate nonbiodegradable conductive nanomaterials that will remain in the human body as foreign matters. Herein, a biodegradable conductive hybrid hydrogel is demonstrated based on the integration of black phosphorus (BP) nanosheets into the hydrogel matrix. To address the challenge of applying BP nanosheets in tissue engineering due to its intrinsic instability, a polydopamine (PDA) modification method is developed to improve the stability. Moreover, PDA modification also enhances interfacial bonding between pristine BP nanosheets and the hydrogel matrix. The incorporation of polydopamine‐modified black phosphorous (BP@PDA) nanosheets into the gelatin methacryloyl (GelMA) hydrogels significantly enhances the electrical conductivity of the hydrogels and improves the cell migration of mesenchymal stem cells (MSCs) within the 3D scaffolds. On the basis of the gene expression and protein level assessments, the BP@PDA‐incorporated GelMA scaffold can significantly promote the differentiation of MSCs into neural‐like cells under the synergistic electrical stimulation. This strategy of integrating biodegradable conductive BP nanomaterials within a biocompatible hydrogel provides a new insight into the design of biomaterials for broad applications in tissue engineering of electroactive tissues, such as neural, cardiac, and skeletal muscle tissues. Abstract : A black phosphorus nanosheet–incorporated gelatin methacryloyl hydrogel is developed as a biodegradable and conductive scaffold for tissue engineering of electroactive tissues. Both the gene expression and protein level assessments indicate that the black phosphorus nanosheet–incorporated biodegradable conductive hydrogel scaffold can significantly promote the differentiation of mesenchymal stem cells into neural‐like cells under the synergistic electrical stimulation.